2015
DOI: 10.1097/aci.0000000000000191
|View full text |Cite
|
Sign up to set email alerts
|

Allergy to honeybee … not only stings

Abstract: Anaphylaxis to bee products is rare. Some studies show a clear association between some aeroallergens such as compositae with allergic reactions to bee products. Additionally, allergic reactions to bee products are associated with severe outcomes in atopic and patients with lung disorders and are a common occupational disease in beekeepers. Possible cross-reactivities have been suggested between bee components and bee venom. Furthermore some studies found patients with concomitant allergy to honey or to propol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 34 publications
2
11
0
Order By: Relevance
“…Total and bee/Vespula venom-specific IgE were measured using the ImmunoCAP method (Thermo Fisher Scientific, Freiburg, vol 50, n 5, 232-234, 2018 prick tests with cooked larvae were suggestive of a certain heat-lability of the causative allergen. The above mentioned considerations are in accordance with reports on IgE-mediated allergy to other bee-products identifying beekeeping, atopy and respiratory diseases as risk factors, whereas clinically relevant cross-reactivity to honey bee venom seems to be an exception (3). Royal jelly is a glandular secretion from worker bees used to feed all kinds of larvae and the adult queen.…”
Section: Case Presentationsupporting
confidence: 83%
See 1 more Smart Citation
“…Total and bee/Vespula venom-specific IgE were measured using the ImmunoCAP method (Thermo Fisher Scientific, Freiburg, vol 50, n 5, 232-234, 2018 prick tests with cooked larvae were suggestive of a certain heat-lability of the causative allergen. The above mentioned considerations are in accordance with reports on IgE-mediated allergy to other bee-products identifying beekeeping, atopy and respiratory diseases as risk factors, whereas clinically relevant cross-reactivity to honey bee venom seems to be an exception (3). Royal jelly is a glandular secretion from worker bees used to feed all kinds of larvae and the adult queen.…”
Section: Case Presentationsupporting
confidence: 83%
“…Of note, one of the above mentioned case reports does not specify the exact composition of the culprit royal jelly preparation referred to as "beverage containing crude royal jelly" (4), therefore giving rise to the question whether contaminating larvae might have been the actual elicitor of anaphylaxis. Major royal jelly proteins 8 and 9 have been identified as glycosylated components of bee venom (Api m11), whereas their clinical relevance for sting-induced anaphylactic reactions remains uncertain (3,8). Furthermore, royal jelly has been recognized as a cause of occupational allergic respiratory disease (9).…”
Section: Case Presentationmentioning
confidence: 99%
“…Remarkably, honeybee venom can cause allergic reactions in sensitized individuals ( 44 46 ). It has been found that even residual amounts of honeybee venom in honey can induce an allergic reaction, which is a very rare condition ( 29 , 47 ). These allergic reactions are triggered mainly by the peptide melittin and the enzymes phospholipase A 2 , A 1 , and hyaluronidase.…”
Section: The Honeybee Venommentioning
confidence: 99%
“…Nevertheless, allergies to honey are reported rather rarely. The actual incidence of allergy in the general population is unknown; it is estimated to be less than <0.001%, and only few cases have been reported (Aguiar et al, 2017;Cifuentes, 2015). This is even more surprising, taking into account that 10-30% of the population in the world are sensitive to aeroallergens (WAO, 2013), whose pollen can also be found in honey.…”
Section: Introductionmentioning
confidence: 99%